ANALISIS TEKS DAN PANORAMA UMUM MAZMUR 87 - Sinaga, Norbeth (UNIKA Santo Thomas, 2012)
Psalm 87 has some filological and textual problems that make difficulties in translating it to other languages. The problems has result in different translations or different meanings in some edition. However, it has becoming an object of study and a base of valutation in making an alternative translation. So, the different translation is not at all an obstacle to profound the psalm. The knowledge of grammatical hebrew’s system, the original text in Textus Masoreticus and different editions or translations help us to understand the disposition of the problems and to determine a new opinion. The understanding of context and theology of the psalm help us to estimate its sitz im leben. The study of the structur facilitates a reader to realize that the psalm is one of the Korahites which has a focus to exalt Jerusalem as a city of God.